Fungal Infections in Patients With Infected Pancreatic Necrosis and Pseudocysts: Risk Factors and Outcome. Issue 1 (January 2018) - Reuken, Philipp A.; Albig, Hanna; Rödel, Jürgen; Hocke, Michael; Will, Uwe; Stallmach, Andreas; Bruns, Tony
Abstract : Objectives: Fungal infections in patients with acute pancreatitis are common and potentially life threatening. Data on fungal pancreatic infections are inconsistent. Therefore, the aim of this study was to identify risk factors for fungal infection and to determine their impact on survival. Methods: This was a retrospective analysis of pathogen spectrum and outcome of infected pancreatic necrosis or pseudocysts from 3 German hospitals from 2002 to 2016. Results: A total of 187 fine-needle aspirations were performed in 113 patients. Fungal pancreatic infections, predominantly caused by Candida species, were identified in 52 patients (46%). Antibiotic treatment before fine-needle aspiration (84.6% vs 49.2%, P = 0.003) and the duration of therapy (9 vs 2 days, P = 0.024) identified patients at an increased risk of fungal infection. Patients with fungal pancreatic infections had a longer hospital stay (34 vs 14 days, P < 0.001), received intensive care treatment more often (55.8% vs 27.9%, P = 0.002), and had a lower 365-day survival (78.4 [SE, 6.6%] vs 95.0 [SE, 2.0%], P = 0.035) than patients with bacterial pancreatic infections only. Conclusions: Fungal infections are common in patients with infected pancreatic necrosis and pseudocysts and indicate patients with a higher risk of mortality in the long term. Abstract : Supplemental digital content is available in the text.